2021
DOI: 10.1007/s00382-020-05554-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rain-shadows in the Ethiopian Mountains using climatological model data

Abstract: Orography is known to affect local meteorological conditions by inducing orographic rainfall and a rain shadow i.e. reduced rainfall on the mountain's leeside with respect to the windward side. Therefore it has a strong effect on the local population and agriculture. Recent work highlights the ambiguities in the definition and difficulties in quantification of the rain shadow effect using observational data. A statistical approach is presented that allows its investigation based on climatological model data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 102 publications
3
43
0
Order By: Relevance
“…While ERA5 is much closer to observations than its predecessor, the horizontal resolution of 0.25°x0.25° can still be considered too coarse for assessing the PWV variability over Ethiopia. Additionally, in order to obtain reliable climate projections, especially for extreme precipitation, climate simulations at convection-permitting resolutions are necessary [21,67]. In this study, in which we wanted to assess the present-day representation of PWV by GPS and ERA5, we are spatially limited by the coverage of the GPS network in Ethiopia, which are mainly "point" observations.…”
Section: Discussionmentioning
confidence: 99%
“…While ERA5 is much closer to observations than its predecessor, the horizontal resolution of 0.25°x0.25° can still be considered too coarse for assessing the PWV variability over Ethiopia. Additionally, in order to obtain reliable climate projections, especially for extreme precipitation, climate simulations at convection-permitting resolutions are necessary [21,67]. In this study, in which we wanted to assess the present-day representation of PWV by GPS and ERA5, we are spatially limited by the coverage of the GPS network in Ethiopia, which are mainly "point" observations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the lack of deviations in the two water towers may indicate the resilience of forested regions (i.e., adaptable nature of forests), as described in Van der Velde et al (2014), Creed et al (2014), and Helman et al (2017. Such resilience (measured as elasticity) could be a key factor in forested water towers, indicating their ability to resist change or bounce back to their initial natural conditions, hence plotting along the reference Budyko curve.…”
Section: Discussionmentioning
confidence: 99%
“…Du et al (2016) demonstrated that the basins in the upper slopes met steady-state conditions, while this was not the case for downstream basins due to human interference and water inflows from the upstream basins. In their study, Van der Velde et al (2014) demonstrated that the climate and land use changes do not outpace the ability of the forests to adapt their water use and energy use strategies to the prevailing conditions. Han et al (2020) studied 1057 global unimpaired catchments and showed that over 70 % of the catchments attain a steady-state within 10 years, with co-evolution between climate and vegetation coverage playing a key role in maintaining the steady-state conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitation has two main seasonal variations, where August to September are the wettest months, while December to April are the driest months. The spatiotemporal rainfall patterns are highly inhomogeneous due to the complex orography and convective nature of rainfall [21]. Moreover, the decadal variability of Ethiopian rainfall is known to be significant [22,23].…”
Section: Study Areamentioning
confidence: 99%